2019
DOI: 10.1093/jpo/joz006
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ‘blue-collar professionalism’: Continuity and change in the professionalization of uniformed emergency services work

Abstract: The sociology of professions has so far had limited connections to emergency services occupations. Research on emergency occupations tends to focus on workplace culture and identity, often emphasizing continuity rather than change. Police officers, firefighters, and paramedics have their historical roots in manual, technical, or ‘semi-professional’ occupations and their working lives still bear many of the hallmarks of blue-collar, uniformed ‘street-level’ work. But uniformed emergency services—like many other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…In line with Kanter's ideas on collaboration as a way to enhance power resources, we found that the closer a communication officer works to the rescue services, the higher the status of the communication officer. Working closely with blue collar professionals (McCann & Granter, 2019) with high credibility among the public, tends to benefit crisis communicators as they can draw from the emergency services' power resources in crisis preparedness, collaboration and legitimacy. Interestingly enough, relations seem to go both ways as emergency service personnel can also be empowered by becoming more skilful communicators.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with Kanter's ideas on collaboration as a way to enhance power resources, we found that the closer a communication officer works to the rescue services, the higher the status of the communication officer. Working closely with blue collar professionals (McCann & Granter, 2019) with high credibility among the public, tends to benefit crisis communicators as they can draw from the emergency services' power resources in crisis preparedness, collaboration and legitimacy. Interestingly enough, relations seem to go both ways as emergency service personnel can also be empowered by becoming more skilful communicators.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Traditional emergency and rescue service professions such as firefighters, police and prehospital medical care are at the forefront of this development. These operators are “educated and trained to handle crises” (Oscarsson & Danielsson, 2018:225) and have for some time been discussed in terms of professions or collectives of professionalizing individuals (Drabek, 1994; McCann & Granter, 2019). Formal education and training drive this development (Wilson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a "participatory turn" (Strandh, 2019, p. 311) in disaster research and policy, which stresses the importance of collaboration between emergency organizations and civil society (McCann & Granter, 2019;McLennan et al, 2016). In disasters, emergency services may be organized into an official disaster response operation (OR), which is "part of the national system of civil protection and preparedness" and which "has a clear organizational structure, is governed by laws and regulations, and takes the form of a workplace, where a number of different actors collaborate in order to respond to the challenges caused by the disaster" (Johansson et al, 2018, p. 3; see Kvarnlöf & Johansson, 2014).…”
Section: Research On Volunteer Participation In Disaster Managementmentioning
confidence: 99%
“…The delineation between this and the concept of emotional labour during the COVID-19 pandemic has been placed in the limelight. Essentially, they belong to the same psychological parameters but, while emotional intelligence is about processing complex information about an emotive response, emotional labour refers to the fact that, in paid employment, personnel are expected by virtue of their professional contracts to behave in a particular manner (McCann and Granter, 2019).…”
Section: Framing Emotional Responsementioning
confidence: 99%